(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This study is a theoretical exploration of the role of digital technologies in the development of critical thinking skills in the context of English as a foreign language education among secondary school students. Although there has been a growing interest in the topic of digital tools and their integration in EFL teaching, there is little research that targets learners at secondary school with a focus on the specific context of Kazakhstan. This study addresses the question: What role can digital technologies play in developing critical thinking in secondary EFL classrooms? A literature review and thematic synthesis of 30 scientific sources, including in-depth analysis of 10 studies examining secondary education. The findings indicate that digital tools including AI-based learning platforms, digital annotation tools and collaborative applications can successfully support higher-order thinking skills when they are implemented with appropriate pedagogical strategies and teacher guidance. However, issues such as digital distraction, superficial engagement, concerns over authenticity and unequal access appear to remain serious challenges. The study addresses this gap in research by providing a conceptual synthesis relating to secondary EFL education and practical implications for teachers and curriculum developers.